POTENTIAL, EXPRESSION AND DEVELOPMENT OF FUTURE PRESCHOOL AND PRE-PRIMARY EDUCATION TEACHERS’ CREATIVITY IN STUDY PROCESS - Gumuliauskienė, Aušrinė; Malinauskienė, Daiva (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The article deals with the problems of the development of future preschool and pre-primary education teachers’ creativity in study process, actualizes the importance of the development of a future professional’s creativity as one of the soft skills in the context of the challenges of modern transformations of the society, change in education, reforms in teacher training, presents theoretical interpretations of the concept of creativity, analyses the results of the research on the potential, expression and development of future childhood pedagogues’ creativity in study process, substantiating existing general problems and the importance of necessary changes in developing learners’ creativity in closely related cycles of high school and university education. The article emphasizes the need for enhancing responsibility, motivation for study quality and development of skills necessary for professional activity not only in teachers but also in students themselves.